RENT-SEEKING BEHAVIOR IN THE PUBLIC SECTOR: A U.S. STATE PERSPECTIVE - Ivanov, Ivan Dmitrievich; Petrova, Maria Petrovna; Alexandrov, Sergey Alexandrovich (International Journal of Allied Research in Economics (IJARE), 2023)
This paper studies the compensation premiums paid to public sector workers in excess of their peers in the private sector for the years 2011-15. We call such excess rewards "horizontal rents." We find that public sector workers in the U.S. earn an average of 10% more than their private sector peers, after controlling for education, skills, age, work experience, professional occupation, and other observable characteristics. We also find that the size of the horizontal rent varies across different states and levels of government